Fusion bonding of structural T-joints for thermoplastic composite boats. (May 2013) - Otheguy, ME; Gibson, AG; Robinson, AM
This article presents an experimental study of fusion-bonded polypropylene (PP) glass composite joints in the context of small craft manufacture. The objective is to investigate the manufacturing of lap joints and T-joints as a structural part of a small boat and study their properties, because a joining technique is a fundamental requirement of any boat construction technology. Results show that PP interlayers improve bond quality for both lap joints and T-joints and that woven precursor materials are preferred for T-joint manufacturing. It was also found that this technique produces higher lap shear strength values than adhesives and resistance welding, and that pull-out strength values were comparable with those of thermosetting designs, demonstrating that fusion bonding is a suitable joining technique for thermoplastic composite craft.